Sr and SrBr2 vapour lasers excited in nanosecond pulsed longitudinal discharge, oscillating on Sr atom and ion transitions - Vuchkov, Nikola Kirilovich (Известия высших учебных заведений. Физика)
Middle infrared high-power stable-operating He–SrBr2 laser IC-excited in nanosecond pulsed longitudinal discharge, was developed and studied. An active volume scaling in bore and length of this laser was carried out. The optimal temperature regime was found for laser oscillation at several different Sr atom and ion lines. Optimal discharge conditions, such as active zone diameter, vapour pressure, buffer-gas pressure, electrical excitation scheme parameters, average input power, pulse repetition frequency, were found. At multiline operation an average output power of 4.30 W was obtained, more than 90 % of which was concentrated on the 6.45-μm Sr atom line. The radial distribution of the laser intensity was detected to be a high-beam-quality Gaussian profile. The laser pulse duration (FWHM) for the He–SrBr2 laser was about 150 ns. This laser equipped with optical system for control of laser radiation parameters, such as laser beam divergence, laser intensity distribution, etc. could be successfully used in a large variety of applications, such as precise ablation or modification of soft and hard biological tissues, determination of optical properties of different materials newly developed instead of free electron lasers. Water-cooled IC-excited Sr+ recombination laser, stable-operating at average output power of 0.8–1.1 W with independent production of Sr vapour, is described. Some features of the discharge tube construction and the laser operation are given. A maximal average laser power of 1.5 W was achieved under transient conditions. The IC-circuitry practically eliminated the detrimental ringing of the tube current and ensured tripling (or more) of the rectifier voltage to be imposed on the tube electrodes. It was found that the application of the water cooling enabled a higher input power loading for optimal tube wall temperature. At Sr+ laser with independent production of the metal vapour it was possible to control the concentration of the Sr vapour and to inhibit the effect of overheating on lasing. Thеse peculiarities resulted in an increase in the average laser power and an improvement of the laser operation stability.